Meta Analysis of the Effect of Mastectomy on Dysfunction Sexuality in Women with Breast Cancer - Rizky Januar Putri Ambayu; Sumiyati Sumiyati (Masters Program in Public Health, 2022)
Background: Breast cancer is cancer that forms in breast tissue, breast cancer occurs when cells in the tissue in the breast grow uncontrollably and take over the healthy breast tissue and its surroundings. Breast cancer has the highest mortality rate due to delay in early detection. In addition, several breast cancer treatments such as lumpectomy surgery, mastectomy, radiotherapy, hormone therapy and chemotherapy have long-term side effects, one of which is sexual dys¬function. This study aimed to estimate the effect of mastectomy on sexual dysfunction in women with breast cancer, with a meta-analysis of primary studies conducted by the previous authors. Subjects and Method: This study was a systematic review and meta-analysis with the following PICO, population: women with breast cancer. Intervention: mastectomy. Comparison: no mastectomy. Outcome: sexual dysfunction. The articles used in this study were obtained from databases, namely Google Scholar, PubMed, and Science Direct. Keywords to search for articles “Breast Cancer” OR “Sexual Dysfunction” OR “Mastectomy” articles included are full-text English and Indonesian with a cross-sectional study design from 2012 to 2021 and report the Adjusted Odds Ratio (aOR) that appropriate in the multivariate analysis. The selection of articles was carried out using the PRISMA flowchart. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 9 cross-sectional studies involving 6,045 breast cancer patients from Spain, China, Turkey, Denmark, America, UAS, Iran, Australia, and Iran were selected for systematic review and meta-analysis. The data collected showed that breast cancer patients who underwent mastectomy had a 1.69 times risk of sexual dysfunction compared to women who did not use the mastectomy treatment method (aOR = 1.69; 95% CI = 0.83 to 3.45: p < 0.001). Conclusion: Women with breast cancer and undergoing mastectomy increase the risk of sexual dysfunction. Keywords: breast cancer, mastectomy, sexual dysfunction. Correspondence: Sumiyati. Universitas ‘Aisyiyah Yogyakarta. Mlangi Nogotirto, Jl. Siliwangi Jl. Ringroad Barat No. 63, Area Sawah, Nogotirto, Gamping, Sleman, Daerah Istimewa Yogyakarta 55592. Email: mia.azizi.ma@gmail.com. Mobile: 082282246211.